Relação da espessura médio-intimal das artérias femorais com doença arterial periférica - Diógenes, Camilo de Alencar (2022)
Introduction: Peripheral arterial disease (PAD) is one of the cardiovascular diseases, in addition to cerebrovascular and coronary ischemic diseases. It is related to arterial atherosclerotic involvement of the lower limbs and determines high morbidity and mortality when not properly diagnosed and treated. Its diagnosis is made through clinical and imaging tests, with the ankle-brachial index being an important diagnostic tool. The index is only altered when the disease is installed, unlike the intima-media thickness (IMT), which may undergo early changes in the course of atherosclerotic disease. Carotid IMT has been widely studied and corresponds to an important marker of systemic atherosclerosis. The present study intends to evaluate the IMT of the femoral arteries and its relationship with PAD. Methods: The research consists of a cross-sectional epidemiological study carried out at the Walter Cantídio University Hospital with a descriptive and analytical approach. Measurements were obtained using B-mode ultrasonography (US) of the IMT of the femoral arteries in eighty-one patients with PAD and eighty-three patients without the disease. Information was collected regarding age, gender and modifiable cardiovascular risk factors, diabetes, hypertension, smoking and dyslipidemia. The measures obtained in the two groups and among the participants of the same group were then compared according to the determined variables. A comparison of arteriography findings of the lower limbs of patients with PAD with cardiovascular risk factors was also performed. Results: There was a significant difference in femoral IMT between participants in both groups, with a mean of 1.22 ± 0.19 mm in the DAP group and 0.85 ± 0.18 mm in the control group (p < 0.01). In addition to the presence of PAD, age and the number of cardiovascular risk factors were strongly associated with higher values of femoral IMT. Regarding the location of the atherosclerotic lesions in patients in the PAD group, it was observed that smoking was more associated with proximal lesions (iliac segment), while diabetes was more associated with distal lesions (tibial-fibular segment). Conclusion: The study demonstrates a positive relationship between femoral IMT and peripheral atherosclerotic disease, considering the higher values obtained in the PAD group. Additional findings observed that age and presence of cardiovascular risk factors were associated with higher values of femoral IMT. Measurement of femoral IMT with US demonstrated good reproducibility and an easy-to-perform technique, which could become a direct complement to the vascular physical examination of the lower limbs. We conclude that patients with increased femoral IMT, even if asymptomatic and with no abnormalities on clinical examination, deserve special attention because of the greater risk of developing PAD over the years.